2007
DOI: 10.1111/j.1469-7998.2006.00271.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of badger latrines in a high‐density population: habitat selection and implications for the transmission of bovine tuberculosis to cattle

Abstract: Eurasian badgers Meles meles habitually deposit droppings and other scent marks at latrines, which may be associated with territorial defence, and communicate information related to group and individual identity and status, and food resources. Understanding patterns of latrine distribution contributes to our understanding of badger social behaviour, and may be relevant to managing the risks of transmission of bovine tuberculosis from badgers to cattle. We investigated the distribution of badger latrines relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
17
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 35 publications
3
17
1
Order By: Relevance
“…Hog badger removal operations to manage rabies (Hu et al 2012) would seem likely to disturb patterns of latrine use and social contacts, potentially causing perturbation effects similar to those reported in other species (Prentice et al 2014), and resonating with lessons from bovine tuberculosis management in European badgers (e.g., Tuyttens et al 2000, Riordan et al 2011. Habitat management, such forestry operations, influence hog badger latrine use, with latrines being used most in logged and selectively-logged forest and least in farmland; this too has implications for disease epidemiology (White et al 1993, Delahay et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…Hog badger removal operations to manage rabies (Hu et al 2012) would seem likely to disturb patterns of latrine use and social contacts, potentially causing perturbation effects similar to those reported in other species (Prentice et al 2014), and resonating with lessons from bovine tuberculosis management in European badgers (e.g., Tuyttens et al 2000, Riordan et al 2011. Habitat management, such forestry operations, influence hog badger latrine use, with latrines being used most in logged and selectively-logged forest and least in farmland; this too has implications for disease epidemiology (White et al 1993, Delahay et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…Latrines are likely to be particularly influential or to have high betweenness in the network if they are either contacted by many individuals of both species or connect individuals that are otherwise unlikely to interact. The fact that boundary latrines (i.e., those located at the boundary between different social group territories, such as node IDs 157 and 169 in the present study) are more likely to be visited by badgers from multiple setts is well established (Roper et al, 1993;Delahay et al, 2007). Our analysis reveals the true importance of this to the overall network structure; boundary latrines are responsible for almost half of the shortest paths through the network between pairs of badgers from different groups.…”
Section: Discussionmentioning
confidence: 67%
“…However, in badger social networks a more in-depth analysis was required to characterise the relationship between network position and infection (Weber et al, 2013b), and therefore it may be that more detailed datasets on badger-latrine-cattle interactions could provide greater insights. There is considerable literature on temporal and individual variation in latrine use by badgers (Roper et al, 1993;Stewart et al, 2002;Delahay et al, 2007), but less information on how and why cattle interact with latrines (but see Benham & Broom, 1991;Hutchings & Harris, 1997). However, it is only by taking the two in combination that the full picture can be revealed, and the use of temporally dynamic methods is likely to be especially illuminating due to the time-lagged nature of transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Like our earlier research [6], we found reduced risks of bTB on farms with greater hedgerow abundance. Badger latrines and urination sites are often associated with woodland edges, hedgerows and walls [15], and it is therefore likely that the availability of these resources limits the contamination of pasture. How closely cattle graze to the boundary features will depend on management practices and grazing pressure, and further work is warranted to assess whether reduced cattle access to these features is effective in reducing bTB risk.…”
Section: Discussionmentioning
confidence: 99%